CONCEPTUAL FUNDAMENTALS OF FREIGHT MAGNETOLEVITATION TRANSPORT SYSTEM CONSTRUCTION (Transport systems and technologies, 2022)
An analysis of the transport systems current state in Ukraine has shown that the main problem in this area is the lack of transport infrastructure capacity, due to low route speeds for most transport modes and low levels of traffic organization and management. The level of rail container transport, the most common and perspective type of freight transportation is also low compared to European countries. Therefore, the main idea of the article is to justify the need for the introduction of fundamentally new transport technologies that will help reduce or eliminate the problems of freight transport, and so the article is relevance. The possibility of using magnetic technologies that exclude contact of a vehicle with a road structure, for freight transportation is investigated. The authors consider the main structural elements, functions and possible options of the magnetic levitation transport system of freight transport. The practical value of the work is that the use of magnetic levitation container platforms will significantly increase the intensity and speed of the conveyor sending of each container with a decrease in energy consumption, which will significantly affect the improvement of cargo logistics. The main results of the work: the conceptual bases of construction of unmanned magnetic levitation vehicles and the main systems of their infrastructure are formulated, it is shown that the implementation of the function of drone for the vehicle is possible only if permanent levitation in all sections of the freight transportation will be provided.
Keywords: freight transportation, speed of movement, magnetic levitation system, unmanned technologies, container platform.